On the photophysics of four heteroleptic iridium(III) phenylpyridyl complexes investigated by relativistic multi-configuration methods. (16th February 2016) - Heil, Adrian; Gollnisch, Kathleen; Kleinschmidt, Martin; Marian, Christel M.
ABSTRACT: In this work, we present a detailed analysis of the photophysical properties of four phosphorescent iridium(III) complexes, i.e. trans -N, N- and cis -N, N-(ppy)2 Ir III (acac) as well as their fluorinated derivatives trans -N, N- and cis -N, N-(F2 ppy)2 Ir III (acac). These properties include absorption and emission characteristics, intersystem crossing rates from the lowest singlet excited state, phosphorescence lifetimes of the individual triplet sublevels as well as the orientations of the transition dipole vectors. To this end, we have carried out combined density functional theory and multi-reference configuration interaction studies including spin–orbit coupling by perturbational as well as variational procedures. For the experimentally known complexes, we observe excellent agreement between our computed data and literature data. Also the blueshifts of the emission maxima occurring upon fluorination of the (ppy)2 Ir(acac) compounds are well reproduced. To our surprise, we find the experimentally not yet investigated cis -N, N-(F2 ppy)2 Ir(acac) isomer to be thermodynamically more stable than the well-known blue phosphorescent emitter trans -N, N-(F2 ppy)2 Ir(acac). Abstract :